An assessment of trade integration focusing on export-led growth strategy for Sarawak: an economic geography perspective - Taasim, Shairil Izwan (Human Resource Management Academic Research Society, 2022)
In an attempt to mitigate domestic supply and increasing local needs and wants for goods and services, international trade is the solution. This paper aims to investigate the development of trade integration focusing on Sarawak as a state in the Federation of Malaysia. The paper employed the gravity model in the context of international trade for Sarawak. Data from selected countries were used covering a period of 10 years. The paper contributes to the gravity model focusing on international trade and economic growth in a state in Malaysia. The findings revealed that Sarawak geographic remoteness contributed to better performance in terms of adding value to its current exports. In the desire to make Sarawak an export led-growth economy, the government has established a Ministry responsible for coordinating and supporting both industrial development and international trade.